Consensus - reference ranges of vitamin D [25(OH)D] from the Brazilian medical societies. Brazilian Society of Clinical Pathology/Laboratory Medicine (SBPC/ML) and Brazilian Society of Endocrinology and Metabolism (SBEM) - Carlos Eduardo S. Ferreira; Sergio S. Maeda; Marcelo C. Batista; Marise Lazaretti-Castro; Leonardo S. Vasconcellos; Miguel Madeira; Lilian M. Soares; Victória Z. C. Borba; Carolina A. Moreira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Vitamin D is considered a pre-hormone and plays a crucial role in calcium homeostasis and, consequently, in bone health. The best source of vitamin D is the skin in response to sunlight. Only small amounts of this vitamin are found in some foods (especially fatty fish), which makes availability of vitamin D in the diet limited. Brazilian population studies show that the prevalence of hypovitaminosis D in our country is high. Objective: To define the reference intervals for vitamin D [25(OH)D]. Discussion: Consensus of specialists - literature review. Conclusion: The standardization of reference intervals is fundamental for the correct diagnosis and treatment of hypovitaminosis D.